GM1 controlled lateral segregation of tyrosine kinase Lck predispose T-cells to cell-derived galectin-1-induced apoptosis - Novák Julianna (MOLECULAR IMMUNOLOGY, 2014)
One prominent immunoregulatory function of galectin-1 (Gal-1), a beta-galactoside binding mammalian lectin, is induction of apoptosis in activated T-cells by a process depending on the activity of Src family tyrosine kinase, Lck. Although the requirement for Lck in Gal-1 induced T-cell death and the ability of Gal-1 to affect the membrane localization of extracellular Gal-1-binding proteins have been well documented, the consequence of the complex and related reorganization of extra- and intracellular signaling components upon Gal-1 treatment of T-cells has not yet been revealed. Therefore, we have analyzed the plasma membrane movement of Lck upon Gal-1 triggered signaling, and the significance of this event in Gal-1 induced T-cell death. Non-receptor tyrosine kinase, Lck primarily localized in the synapse of tumor cell-T-cell during 15min of the established direct cell contact. Later, after 30min, a lateral segregation of Lck from the cell synapse was observed. The migration of Lck to the opposite of the cell contact apparently depended on the expression and cell surface presentation of Gal-1 on the effector (tumor) cells and was accompanied by phosphorylation on the negative regulatory tyrosine residue, Tyr505. Receptor tyrosine phosphatase, CD45 played crucial role in this event since CD45 deficiency or inhibition of its phosphatase activity resulted in the failure of Lck membrane movement. Level of the Gal-1-binding glycolipid GM1 ganglioside also essentially regulated Lck localization. Segregation of Lck and Gal-1 induced apoptosis was diminished in T-cells with low GM1 expression compared to T-cells with high GM1. Our results show that spatial regulation of Lck by CD45 and GM1 ganglioside determines the outcome of apoptotic response to Gal-1 and this local regulation may occur only upon intimate effector (Gal-1 expressing) cell-T-cell attachment.